Microscopic use-wear and residue analysis of stone reamers recovered from the early Holocene layer of the Eel Point site (CA-SCLI-43) on San Clemente Island, California. (June 2019) - Cassidy, Jim; Kononenko, Nina; Robertson, Gail; Raab, L. Mark
Abstract: The Eel Point site on San Clemente Island is the earliest occupation known for the southern Channel Islands of California. Excavations in the early Holocene layer yielded stone tools scattered over a 9 m 2 area. These tools include drills, reamers, scrapers, abraders, spoke-shave, macroblade plane, burin, wood-splitting wedges and a modified sea mammal rib with asphalt stains. Examination of technological attributes and microscopic use-wear patterns initially concluded the tools were used for wood-working. Further microscopic residue analysis conducted on the twelve reamers identified the remains of woody plant materials, ocher and asphalt. No other residues, including stone, shells or fauna were found. The absence of trees in this location suggests the tools were employed in working on imported wood materials, such as those used in watercraft required to transport people to and from the island. The findings herein support the hypothesis that these specific wood-working stone tools, found in close proximity to each other represent an early Holocene watercraft construction or maintenance tool-kit. Highlights: The 9000-year-old occupation at Eel Point is the oldest occupation known for the southern Channel Islands of California. The early Holocene layer at Eel Point contained a specialized wood-working tool-kit concentrated within a 9 m 2 area. A dozen stone reamers represented 41% of the wood-working tool-kit. Residue analysis identified soft woods, ocher and asphalt as the only materials processed by the stone reamers. The wood-working tool-kit, including reamers, is technologically consistent with construction of composite watercraft.